Analysis of the Precision, Robustness, and Speed of Elastic Resonator Interference Stress Microscopy - Liehm, Philipp (Biophys J, 2018)
Localization-microscopy-based methods are widely used to map the forces that cells apply to their substrates and to study important questions of cellular biomechanics. By contrast, elastic resonator interference stress microscopy (ERISM) uses an interference-based approach, which requires low light intensity and facilitates imaging of cellular forces with extreme precision (down to pN forces) and robustness (e.g., for continuous force monitoring over weeks). Here, the measurement trade-offs and numerical considerations required to optimize the performance of ERISM are described. The crucial parts of the fitting algorithm and the computational tools used to evaluate the data are explained in detail, and the precision and accuracy achievable with ERISM are analyzed. Additional features that can improve the robustness of ERISM further are discussed. The implementation of the analysis algorithm is verified with simulated test data and with experimental data. In addition, an approach to increase the acquisition speed of ERISM by a factor of four compared to the original implementation is described. In combination, these strategies allow us to measure the forces generated by a neural growth cone with high temporal resolution and continuously over several hours.